Maximum vertical height during wing flapping of laying hens captured with a depth camera. - Tessa Grebey; Valentina Bongiorno; Junjie Han; Juan Steibel; Janice M Siegford (PLoS ONE)
Cage-free housing systems for laying hens, and their accompanying guidelines, legislation, and audits, are becoming more common around the world. Cage-free regulations often specify requirements for floor space and cage height, but the availability of three-dimensional space can vary depending on system configurations. Little research has looked at how much vertical space a hen occupies while flapping her wings, which is arguably her most space-intensive behavior. Therefore, the objective of this study was to use a depth sensing camera to measure the maximum vertical height hens reach when wing flapping without physical obstructions. Twenty-eight individually caged Hy-line W36 hens at 45 weeks of age were evaluated. A ceiling-mounted depth camera was centered above a test pen and calibrated prior to collecting data. During testing, one hen at a time was placed in the test pen and recorded flapping her wings. From depth footage, the minimum distance between pixels was obtained for each frame, and we computed the maximum vertical height reached by each hen. Results for vertical space used during a wing flapping event showed that hens reached a maximum height of 51.0 ±  4.7 cm. No physical measures taken from hens correlated with maximum height obtained from the depth camera (P > 0.05). Hens in this study were from a single strain, were old enough to have keel damage, and were cage-reared and housed, preventing us from generalizing the results too far. However, depth cameras provide a useful approach to measure how much space laying hens of varying strains, ages, and rearing/housing methods need to perform dynamic behaviors.